Comparative analysis of saturation flow using various PCU estimation methods - Mondal S.; Arya V.K.; Gupta A.; Gunarta S. (My University, 2025)
The magnitude and nature of traffic flow in developing countries are difficult to evaluate due to its mix traffic conditions. In transportation network, intersection plays a vital role to increase the efficiency of the entire road network. Analysis of these nodal points (intersection) is required to evaluate the performance of the intersection through the assessment of operational parameters such as saturation flow and its level of service (LOS). However, the complexity of discharge flow in Indian scenario is mainly due to its mixed properties of traffic stream where both motorized and non-motorized vehicles are traveling in the same stretch without any lane discipline. Also, no single vehicle dominates the traffic stream consequently prediction of saturation flow is more sensitive to that mixed traffic. The passenger car unit is a common platform for the conversion of mixed traffic into a standard unit by taking passenger car as a conventional vehicle. The present study focuses towards the analysis saturation flow at signalized intersection using various PCU estimation methods under mixed traffic conditions. A detailed comparison of the saturation flow obtained by the each methodology with standard saturation flow value given in HCM (2010) is also presented. Traffic and vehicular data were collected from six signalized intersections from three Indian cities such as Delhi, Chandigarh and Allahabad using video graphic method. The prospective method resulted in a lower difference in saturation flow respect to HCM (2010) is proposed for non-lane based mixed traffic stream. © 2020 The Authors. Published by Elsevier B.V.